PERILAKU ANGGOTA KELUARGA DAN LINGKUNGAN DENGAN TINGKAT KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE MENGGUNAKANMETODE STUDY LITERATUR RIVIEW - Jumiyati Jumiyati; Solihati Solihati (Nusantara Hasana Berdikari, 2021)
Dengue Hemorrhagic Fever (DHF) is a dangerous infectious disease that is characterized by fever and bleeding. Dengue fever is transmitted through the bite of the Aedesaegypti mosquito that lives in and around the home environment caused by dengue virus. Poor behavior such as hanging clothes carelessly and the environment which includes ventilation with breeding place and resting place. Therefore Dengue Fever is still a dangerous disease that results in death. Purpose: From this Riview Literature to determine the incidence rate of Dengue Hemorrhagic Fever (DHF) regarding family members' behavior and the environment, so as to solve problems that have occurred in the Community. Research methods: The method used in this study is to search for journal articles in a database using keywords according to topic. Results and Conclusions: There are behaviors that are categorized as not good, such as the habit of hanging clothes carelessly, causing a high incidence of vDengue Hemorrhagic Fever (DHF). As well as the home environment which includes Ventilation, Breeding place and Resting Place. behavior towards cleanliness and the environment is very important to prevent the occurrence of diseases caused by bad behavior and unclean environment. suggestion: Provision of education about transmission and prevention of dengue fever should be further increased to reduce the occurrence of sufferers of Dengue Hemorrhagic Fever (DHF).